Sex Differences in the Utilization and Outcomes of Surgical Aortic Valve Replacement for Severe Aortic Stenosis. Issue 9 (21st September 2017) - Chaker, Zakeih; Badhwar, Vinay; Alqahtani, Fahad; Aljohani, Sami; Zack, Chad J.; Holmes, David R.; Rihal, Charanjit S.; Alkhouli, Mohamad
Abstract : Background: Studies assessing the differential impact of sex on outcomes of aortic valve replacement (AVR) yielded conflicting results. We sought to investigate sex‐related differences in AVR utilization, patient risk profile, and in‐hospital outcomes using the Nationwide Inpatient Sample. Methods and Results: In total, 166 809 patients (63% male and 37% female) who underwent AVR between 2003 and 2014 were identified, and 48.5% had a concomitant cardiac surgery procedure. Compared with men, women were older and had more nonatherosclerotic comorbid conditions including hypertension, diabetes mellitus, obstructive pulmonary disease, atrial fibrillation/flutter, and anemia but fewer incidences of coronary and peripheral arterial disease and prior sternotomies. In‐hospital mortality was significantly higher in women (5.6% versus 4%, P <0.001). Propensity matching was performed to assess the impact of sex on the outcomes of isolated AVR and yielded 28 237 matched pairs of male and female participants. In the propensity‐matched groups, in‐hospital mortality was higher in women (3.3% versus 2.9%, P <0.001). Along with vascular complications and blood transfusion (6% versus 5.6%, P =0.027 and 40.4% versus 33.9%, P <0.001, respectively). Rates of stroke, permanent pacemaker implantation, and acute kidney injury requiring dialysis were similar (2.4% versus 2.4%, P =0.99; 6% versus 6.3%, P =0.15; and 1.4% versus 1.3%, P =0.14, respectively). Length of stay median and interquartile range were both similar between groups (7±6 days). Rates of nonhome discharge were higher among women (27.9% versus 19.6%, P <0.001). Conclusions: Women have worse in‐hospital mortality following AVR compared with men. Coupled with the accumulating evidence suggesting higher magnitude of benefit of transcatheter AVR over AVR in women, women should perhaps be offered transcatheter AVR over AVR at a lower threshold than men.